Quotas and Quality: The Effect of H-1B Visa Restrictions on the Pool of Prospective Undergraduate Students from Abroad - Takao Kato; Chad Sparber (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2010)
In deliberating whether to pursue an undergraduate education in the US, a foreign student takes into consideration the expected probability of securing US employment after graduation. The H-1B visa provides a primary means of legal employment for collegeeducated foreign-nationals. In October 2003, the government drastically reduced the number of available H-1B visas, hence lowering the probability of a college-educated foreign-national finding employment, and possibly discouraging highly qualified international students from attending US colleges and universities. However, citizens from five countries are de facto exempt from the 2003 H-1B visa restrictions. Using international students from these five exempt nations as the control and other international students as the treatment group, we study the effects of the 2003 H-1B policy change on the pool of international applicants to US schools. We use two datasets: (i) College Board SAT score data on prospective international applicants; and (ii) SAT and high-school GPA data on international applicants to a single highly selective university. Our fixed effect estimates show that the restrictive immigration policy has had an adverse impact on the quality of prospective international applicants, reducing their SAT scores by about 1.5%. This effect is driven mostly by a decline in the number of SAT score reports sent by international students at the top-quintile of the SAT score distribution, suggesting that the restrictive immigration policy disproportionately discourages high-ability international students from attending US schools. Our results are robust to alternative specifications, including the use of high-school GPA as a measure of applicant ability
Keywords: F22; I20; O15; I28; J61; 330; Skilled Immigration; H-1B Visa; College Education; SAT Scores